Multimodal prehabilitation enhances perioperative outcomes in gastric cancer patients: a single-center randomized controlled trial - Mu, Guang-Chuan; Tu, Yuan-Hui; Xie, Hai-Lun; Liu, Si-Yu; Jia, Kui; He, Min-Ying; Chen, Ye-Yang; Chen, Jun-Qiang (Frontiers in Nutrition, 2026)
IntroductionMultimodal prehabilitation, integrating exercise, nutrition, and psychological support, has shown value in perioperative care for gastrointestinal cancers, but its efficacy—especially as a short-course intervention tailored to gastric cancer’s need for timely surgery—remains insufficiently validated.MethodsEligible patients undergoing radical gastrectomy received either a 1-week multimodal prehabilitation program plus standard perioperative care (prehabilitation group) or standard perioperative care alone (control group). Primary endpoint was the 30-day postoperative complication rate; secondary endpoints included functional capacity, patient-reported outcomes, recovery metrics, and hospital stay.ResultsRecruitment was conducted from July 2022 to July 2024. A total of 150 patients were randomized, with 131 completing the trial (66 in the prehabilitation group, 65 in the control group). Baseline demographics (gender, age, education level) and clinical characteristics (comorbidities, TNM staging, surgical details) were comparable between groups (all p > 0.05). For the primary endpoint, the prehabilitation group had a significantly lower 30-day overall complication rate (9.1% vs. 26.2%, p = 0.010), with the largest reduction in pulmonary infections (6.1% vs. 21.5%, p < 0.05). For secondary endpoints, the prehabilitation group showed earlier time to first flatus (58.32 ± 26.82 vs. 89.55 ± 26.14 h, p < 0.001), shorter interval to oral intake (48.43 ± 31.98 vs. 105.85 ± 57.36 h, p < 0.001), reduced time to ambulation (25.14 ± 10.63 vs. 38.99 ± 21.01 h, p < 0.001), and shorter postoperative hospital stay (7.76 ± 1.57 vs. 9.77 ± 3.80 days, p < 0.001). They also had superior preoperative 6MWD (448.60 ± 103.65 vs. 362.43 ± 91.85 m, p < 0.001), higher preoperative caloric (25.21 ± 6.33 vs. 16.34 ± 4.44 Kcal/kg IBW, p < 0.001) and protein intake (1.24 ± 0.35 vs. 0.62 ± 0.25 g/kg IBW, p < 0.001), higher discharge QoR-40c scores (p < 0.05), and lower Hospital Anxiety and Depression Scale (anxiety: p = 0.026, depression: p < 0.001) and Fatigue Severity Scale scores (p = 0.003).ConclusionMultimodal prehabilitation (integrating exercise, nutrition, and psychological support) significantly improves perioperative outcomes in gastric cancer patients—including reducing postoperative complications, accelerating functional recovery, and enhancing psychological well-being.Clinical trial registrationClinicalTrials.gov identifier ChiCTR2200062938.